Effects of Static Stretching With High-Intensity and Short-Duration or Low-Intensity and Long-Duration on Range of Motion and Muscle Stiffness - Fukaya, Taizan; Kiyono, Ryosuke; Sato, Shigeru; Yahata, Kaoru; Yasaka, Koki; Onuma, Remi; Nakamura, Masatoshi (Frontiers in Physiology, 2020)
This study investigated the effects of static stretching (SS) delivered with the same load but using two protocols – high-intensity and short-duration and low-intensity and long-duration – on range of motion (ROM) and muscle stiffness. A total of 18 healthy students participated in the study. They randomly performed high-intensity and short-duration (120% and 100 s) or low-intensity and long-duration (50% and 240 s) SS. Outcomes were assessed on ROM, passive torque at dorsiflexion ROM, and shear elastic modulus of the medial gastrocnemius before and after static stretching. The results showed that ROM increased significantly at post-stretching compared to that at pre-stretching in both high-intensity and short-duration [+6.1° ± 4.6° (Δ25.7 ± 19.9%)] and low-intensity and long-duration [+3.6° ± 2.3° (Δ16.0 ± 11.8%)]. Also, the ROM was significantly higher at post-stretching in high-intensity and short-duration conditions than that in low-intensity and long-duration. The passive torque at dorsiflexion ROM was significantly increased in both high-intensity and short-duration [+5.8 ± 12.8 Nm (Δ22.9 ± 40.5%)] and low-intensity and long-duration [+2.1 ± 3.4 Nm (Δ6.9 ± 10.8%)] conditions, but no significant differences were observed between both conditions. The shear elastic modulus was significantly decreased in both high-intensity and short-duration [−8.8 ± 6.1 kPa (Δ − 38.8 ± 14.5%)] and low-intensity and long-duration [−8.0 ± 12.8 kPa (Δ − 22.2 ± 33.8%)] conditions. Moreover, the relative change in shear elastic modulus in the high-intensity and short-duration SS was significantly greater than that in low-intensity and long-duration SS. Our results suggest that a higher intensity of the static stretching should be conducted to increase ROM and decrease muscle stiffness, even for a short time.